Influence of Selected Motivational Factors on Job Satisfaction among Support Staff in Secondary Schools in Rarieda Sub-County - Odak, Elijah Otieno (JOOUST, 2015)
Despite, the fact that support staff play a significant role in school activities, their contribution has not been given serious recognition. The recent report by an Education Task Force was an indication that they were poorly remunerated and their welfare not catered for by our schools. Therefore, their work morale is low and this the justification for the study. The purpose for this study was to explore the influence of selected motivational factors on job satisfaction among support staff secondary schools in Rarieda Sub-County. The objectives of the study were: to determine the relationship between salary structure and job satisfaction, to establish the relationship between rewards strategy and job satisfaction, to find out the relationship between promotion policy and job satisfaction and to determine the relationship between gender and age difference on job satisfaction among support staff in secondary schools in Rarieda Sub-County. Correlational research design was used and the target population was 756 including: 327 support staff, 390 members of Board of Management and 39 school principals. Simple random sampling method was used in selecting 109 support staff, 39 members of B.O.M and 13 Principals were selected through purposive sampling method. Participating schools were selected using stratified random sampling method. Data collection tools included: questionnaires, interview guides and documentary analysis. Validity of research instruments was examined by expert judgement of lecturers of Jaramogi Oginga Odinga University of Science and Technology. Reliability of questionnaires was reported as r = 0.947. Quantitative data was analyzed by descriptive and inferential statistics while qualitative data was analyzed by Thematic analysis. The study findings were that: there was a significant relationship between salary structure and job satisfaction among support staff, there was a significant relationship between rewards strategy and job satisfaction among support staff, there was a significant relationship between promotion policy and job satisfaction among support staff and there was an insignificant relationship between gender and age differences on job satisfaction among support staff. The study recommended that: Board of Management should frequently review salaries of support staff to enable meet their financial needs, the B.O.M should design an elaborate and attractive rewards system to retain their staff and the Ministry of Education, Science and Technology should ensure schools adhere to its guidelines on employment and terms of service for support staff. Further, research should be done on the effects of school principals' leadership styles on support staff job satisfaction and the role of support staff in academic performance in secondary schools.